Perbandingan PAPR Metode CSLM dan SSLM pada Pengirim OFDM - Rana Nuriadnyana; Arfianto Fahmi; Budi Syihabuddin (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2019)
OFDM has multiple weaknesses, one of which is a high Peak to Power Average (PAPR). The maximum power value of the OFDM signal will be much greater than the average power, so the efficiency of the amplifier will be reduced. A popular and effective method to reduce PAPR values is by using Conventional Selected Mapping (CSLM). The CSLM method utilizes the PAPR sensitivity to phase rotation by multiplying the signal that will enter IFFT against different phase rotations and then selects the signal with the lowest PAPR. However, to detect the signal to be selected, the CSLM method requires Side Information (SI) transmission. The method called Symmetric Selected Mapping (SSLM) has been introduced to reduce PAPR values in DCO-OFDM systems without sacrificing bandwidth efficiency caused by SI transmission. The technique on SSLM multiplies signals that will be sent with additional magnitude and different phase rotations. This paper designs OFDM transmitters using Hermitian Symmetry and then analyzes the results of PAPR value reduction using SSLM and CSLM methods. The simulation results show that the PAPR value using CSLM and SSLM methods can reduce PAPR by 3.08 and 3.04 dB.